Parametric Biodigital Inspired Tessellation for Mass Customized Digital Fabrication - Riekstins, Arne (Landscape Architecture and Art, 2021)
This paper researches the limits of repeating patterns that tesselate in a more artistic way for architectural application that is not limited to creating regular triangular, rectangular or hexagonal pieces with decorative purpose and sole material usage. Digitally parametric modeling and CAD-CAM paradigm with input-output sensorial microcontrollers, have brought the possibility to explore the limits of mixing up manual and automatized fabrication techniques with the infinite geometrical potential, implementing AI features. The applied research is being materialized into a mixed technique grayscale concrete floor-tiling prototype featuring concepts of passive flame-imitated indirect red light to enhance health benefits (Arduino microcontroller operated) and zero-waste manufacturing by carrying out CNC milling positive cast to a rubber mold to create an exact amount of geometrically matching pieces needed for the design.